Time Perception and Psychiatric Disorders - Hatice Ceviz; Can Tutug; Nil Banu Bahadirli; Okan Caliyurt (Psikiyatride Güncel Yaklaşımlar, 2013)
Time perception is an ability which we use in every moment of daily life, that guides the formation and continuation of our behaviors and from an evolutionary perspective ensures survival. Internal clock models help us to understand time perception. Time perception is known to vary between individuals and particular situations. This variability is explained with the mechanisms which is associated with the processes related to attention, the speed of the internal clock and the memory unit. It is suggested that time perception is mainly associated with the activities of dopamine and acetylcholine. Some dopaminergic psychoactive substances like cocaine and amphetamine have all been shown to change time perception by increasing the speed of internal clock while on the other hand some antipsychotic drugs make an opposite change in time perception by descreasing the speed of the clock. Similarly, time perception is affected in some psychiatric disorders and an ethiopathological relationship between time perception disturbances and psychiatric disorders is suggested. In this article time perception changes in schizophrenia, attention deficit/hyperactivity syndrome, depression, anxiety disorders and personality disorders are briefly reviewed.